Etiologies associated with chronic cough and its clinical characteristics in school-age children - Yu, Xingmei; Kong, Lingjun; Jiang, Wujun; Dai, Yinfang; Wang, Yuqing; Huang, Li; Luo, Wei; Lai, Kefang; Hao, Chuangli (Journal of Thoracic Disease, 2019)
Background: To comprehensively evaluate the etiology of chronic cough and the value of clinical feature in school age children in Suzhou, China. Methods: School-age (6–14 years) children newly referred with chronic cough (>4 weeks) were prospectively evaluated by utilizing a diagnostic algorithm in this study. Clinical features of different etiologies of chronic cough were also investigated. Results: In total, 118 patients were enrolled in the study. The cough duration ranged from 1 to 76 months. Upper airway cough syndrome (UACS) was found in 77 (65.3%) patients with chronic cough, cough-variant asthma (CVA) in 57 (48.3%) patients, protracted bronchitis (PB) in 15 (12.7%) patients, gastroesophageal reflux disease (GERD) in 7 (5.9%) patients, tic disorders (TD) in 3 (2.5%) patients and eosinophilic bronchitis (EB) in 2 (1.7%) patients. A single etiology was present in 75 patients and multiple etiologies were present in 43 patients. The three most common single etiologies were UACS (31.4%), CVA (14.4%), and PB (10.2%), followed by GERD (5.9%), and EB (1.7%). The most common multiple etiology was CVA + UACS (31.4%), followed by CVA + PB (2.5%), and TD + UACS (2.5%). Conclusions: The common etiologies of chronic cough in school-age children were UACS, CVA, and PB, while EB and GERD were rare.